A Maximum Rupture Model for the Southern San Andreas and San Jacinto Faults, California, Derived From Paleoseismic Earthquake Ages: Observations and Limitations. Issue 15 (27th July 2020) - Scharer, Katherine M.; Yule, Doug
Abstract: Paleoseismic rupture histories provide spatiotemporal models of earthquake moment release needed to test numerical models and lengthen the instrumental catalog. We develop a model of the fewest and thus largest magnitude earthquakes permitted by paleoseismic data for the last 1, 500 years on the southern San Andreas and San Jacinto Faults, California, USA. The largest geometric complexity appears to regulate the system: Only two ruptures break the San Gorgonio Pass region, followed by episodes of ruptures that could bridge the northern San Jacinto Fault and the San Andreas Fault. When tested against independent data on slip per event, the model produces comparable values indicating the end‐member model does not underpredict rupture rates. Rupture of >85% of the fault length in the historic period between 1800 and 1857 and the subsequent quiescence is similar to epochs of activity in the prehistoric model, suggesting that regional clustering of seismicity could be a trait of the system. Plain Language Summary: Large, damaging earthquakes are rare, so geologic data are essential to supplement the record of earthquakes from seismographs. We use the geologic record to determine the magnitude and timing of past earthquakes on the San Andreas and San Jacinto Faults. A pattern emerges in which the biggest bends and splays control the length of most ruptures. Because the model estimates the largest‐possible earthquakes on this system, it is useful as an upper limit on earthquake size used in engineering and earthquake forecasting. Key Points: End‐member model examines the fewest, but longest, ruptures required by ages of ground‐rupturing earthquakes from 31 paleoseismic sites Regional clustering emerges, with largest moment release ruptures similar to the historic record with ruptures breaking much of the system Ruptures through San Gorgonio Pass are infrequent, and anticorrelated with episodes when fault sections near Cajon Pass are active